1995
DOI: 10.1159/000266363
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Singer’s High Formant in Different Type of Singing Voices

Abstract: The presence of singer’s high formant (SHF) in singers of different musical styles was investigated. The voices of 10 opera, 8 folk, 4 pop singers and 53 (nonsinging) controls were recorded. The vowel ‘a’ was sung in three different registers. The percent of energy in the range of SHF and the stability of the pitch period generation were evaluated. The signals of all the singers are characterized by very high stability of the pitch period generation (> 99%), but their formant structures differ considerably. En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…As for the singer's formant, the specific presence in male classic singers is again in accordance with expectation based on comparisons of singing styles in the literature: eg, Doskov et al 35 already observed a stronger singer's formant in opera singers than in folk and pop singers. Traditional explanations pertain to the repertoire, the orchestral accompaniment, the working demands, and the environment (amplification), 4 but the difference in vocal (and musical) education level and in professionalism is an obvious possible bias, that could only be avoided in this study by a selective recruitment.…”
Section: E6supporting
confidence: 88%
“…As for the singer's formant, the specific presence in male classic singers is again in accordance with expectation based on comparisons of singing styles in the literature: eg, Doskov et al 35 already observed a stronger singer's formant in opera singers than in folk and pop singers. Traditional explanations pertain to the repertoire, the orchestral accompaniment, the working demands, and the environment (amplification), 4 but the difference in vocal (and musical) education level and in professionalism is an obvious possible bias, that could only be avoided in this study by a selective recruitment.…”
Section: E6supporting
confidence: 88%
“…A broader understanding of the singing voice has to involve investigating the acoustics of many non-classical styles, and some contributions have been made already on styles as diverse as pop (Schutte and Miller, 1993;Doskov et al, 1995;Thalén and Sundberg, 2001;Borch and Sundberg, 2002), Broadway/musicals (Thalén and Sundberg, 2001;Stone et al, 2003), country & western (Burns, 1986;Stone et al, 1999;Sundberg et al, 1999;Cleveland et al, 2001), jazz and blues (Thalén and Sundberg, 2001), Estonian folk (Ross, 1992), belting (Estill et al, 1994), and overtone singing (Bloothooft et al, 1992;Klingholz, 1993;Lindestad et al, 2001;Van Tongeren, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements derived from the VRP are useful in identifying voices which are well-equipped; in the diagnosis of vocal dysfunction; in suggesting starting points for voice training and in controlling training effectiveness or outcomes of the treatment. Some authors have emphasized an importance of energy measurement in the singers' formant region for an assessment of voice training effects, especially in case of solo singers [18][19][20]31]. However, the following main question remains: which of the methods and voice parameters are the most sensitive to voice training and could better quantitatively describe voice quality, as well as assess voice training effect.…”
Section: Discussionmentioning
confidence: 99%